Drug-Related Problems in the transitional care of the elderly from hospital to home - Silvia Helena Valente; Sara Maria Barbosa; Denise Ferro; Luciana Aparecida Fabriz; Tatiele Estefani Schönholzer; Ione Carvalho Pinto
ABSTRACT Objective: To identify the knowledge produced on Medication-Related Problems in the transitional care of the elderly from hospital to home. Method: Integrative review of the literature data, organized in six stages: guiding question; establishment of inclusion and exclusion criteria; extraction of data; analyze; interpretation of results; and presentation of the review. Articles were considered among 2002 and 2017, in Portuguese, English, and Spanish, in the databases LILACS, MEDLINE, CINAHL and EMBASE. Results: 10 studies were selected and analyzed. They were categorized by subject and identified in three themes: Medication Discrepancy and Reconciliation (40%); Adhesion to Medication (30%); and Adverse Drug Events (30%). Final considerations: Drug-Related Problems in the transitional care of the elderly from hospital to home, were presented as a relevant theme for nursing, involving complex issues related to care. Drug reconciliation was evidenced as a coherent and effective strategy in home care transitions for the elderly.